Structural brain anomalies in Cri-du-Chat syndrome: MRI findings in 14 patients and possible genotype-phenotype correlations. (September 2020) - Villa, R.; Fergnani, V.G.C.; Silipigni, R.; Guerneri, S.; Cinnante, C.; Guala, A.; Danesino, C.; Scola, E.; Conte, G.; Fumagalli, M.; Gangi, S.; Colombo, L.; et al.
Abstract: Introduction: Cri-du-Chat Syndrome (CdCS) is a genetic condition due to deletions showing different breakpoints encompassing a critical region on the short arm of chromosome 5, located between p15.2 and p15.3, first defined by Niebuhr in 1978. The classic phenotype includes a characteristic cry, peculiar facies, microcephaly, growth retardation, hypotonia, speech and psychomotor delay and intellectual disability. A wide spectrum of clinical manifestations can be attributed to differences in size and localization of the 5p deletion. Several critical regions related to some of the main features (such as cry, peculiar facies, developmental delay) have been identified. The aim of this study is to further define the genotype-phenotype correlations in CdCS with particular regards to the specific neuroradiological findings. Patients and methods: Fourteen patients with 5p deletions have been included in the present study. Neuroimaging studies were conducted using brain Magnetic Resonance Imaging (MRI). Genetic testing was performed by means of comparative genomic hybridization (CGH) array at 130 kb resolution. Results: MRI analyses showed that isolated pontine hypoplasia is the most common finding, followed by vermian hypoplasia, ventricular anomalies, abnormal basal angle, widening of cavum sellae, increased signal of white matter, corpus callosum anomalies, and anomalies of cortical development. Chromosomal microarray analysis identified deletions ranging in size from 11, 6 to 33, 8 Mb on the short arm of chromosome 5. Then, we took into consideration the overlapping and non-overlapping deleted regions. The goal was to establish a correlation between the deleted segments and the neuroradiological features of our patients. Conclusions: Performing MRI on all the patients in our cohort, allowed us to expand the neuroradiological phenotype in CdCS. Moreover, possible critical regions associated to characteristic MRI findings have been identified. Highlights: Cri-du-Chat Syndrome (CdCS) is a clinically recognizable syndrome ascribed to deletions in the short arm of chromosome 5. Structural brain malformations have been reported in CdCS patients, but their presence has not been studied systematically. The most common findings are: isolated pontine hypoplasia, vermian hypoplasia, ventricular and corpus callosum anomalies. The study confirms the presence of polymicrogyria (reported once) and optical nerves hypoplasia (never reported). The study suggests a genotype-phenotype correlations, finding a smallest region of overlap, linked with pontine hypoplasia.